Strategies for Human Resources Information System Management with Work Unit-Based Performance Management - Ridwan Setiadi; Muharman Lubis; Mochamad Teguh Kurniawan (Green Publisher Indonesia, 2025)
Effective human resource management (HRM) is crucial for enhancing organizational performance, especially in the digital transformation era. Many Indonesian institutions still use uniform administrative performance management systems without considering the specific functions and tasks of work units. This research aims to design an HRIS management strategy with work unit-based performance management to improve fairness, transparency, and employee motivation. A qualitative case study was conducted at University XYZ in West Java, focusing on non-teaching staff in one faculty. Data were collected through in-depth interviews with 15 informants, document analysis, and direct observation. Thematic analysis identified three main problems: (1) uniform performance assessments that do not accommodate work unit task diversity, (2) low integration of IT and performance assessment systems, and (3) lack of objectivity and transparency in the evaluation process. Based on these findings, the research proposes an HRIS design with a work unit-specific KPI module, real-time performance monitoring dashboard, automated evaluation workflow, and transparent reporting system. The system architecture follows a three-tier model: presentation layer, application layer, and data layer. The implementation of this HRIS is expected to improve performance assessment accuracy by 35%, reduce administrative time by 40%, and increase employee satisfaction with the evaluation system by 50%. This research contributes to HRM literature, especially in integrating information systems with contextual performance management, and offers guidelines for designing fairer and more effective performance assessment systems in higher education.